On the Asymptotic Integration of a System of Linear Differential Equations with a Small Parameter in the Coefficients of a Part of Derivatives - Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We propose an asymptotic method for the integration of one type of systems of linear differential equations with a small parameter in the coefficients of a part of derivatives.